Implikasi Tanda Waqaf terhadap Penafsiran Ayat Iddah dalam Surah Al-Baqarah Ayat 228 - Syahputra, Afrizal El Adzim; Fanani, Mochammad Rizal (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study examines the implications of waqf signs on the interpretation of the verse concerning the waiting period (iddah) for women in Surah Al-Baqarah verse 228. Waqf signs in the Qur'anic manuscript are not merely technical reading guides but also carry significant interpretative functions, especially in legal verses. The purpose of this research is to analyze the role of the al-waqfu awlā sign in separating two distinct legal structures within the verse: the regulation of the iddah period and the prohibition of concealing pregnancy. This research employs a qualitative method with a library research approach. Primary data consist of Surah Al-Baqarah: 228 from the standard Mushaf in the narration of Ḥafṣ from ʿĀṣim, while secondary data are drawn from classical and modern exegesis, tajwīd texts, and fiqh literature. Data were collected through documentation and analyzed descriptively using thematic interpretation and semiotic analysis. The results show that the placement of the al-waqfu awlā sign directly influences the segmentation of meaning in the verse and determines the scope of the legal interpretations derived from it. The study concludes that waqf signs have epistemological value in the construction of Islamic legal exegesis.